The effects of an articulated ankle-foot orthosis with resistance-adjustable joints on lower limb joint kinematics and kinetics during gait in individuals post-stroke. (November 2018) - Kobayashi, Toshiki; Orendurff, Michael S.; Hunt, Grace; Gao, Fan; LeCursi, Nicholas; Lincoln, Lucas S.; Foreman, K. Bo
Abstract: Background: Resistance is a key mechanical property of an ankle-foot orthosis that affects gait in individuals post-stroke. Triple Action® joints allow independent adjustment of plantarflexion resistance and dorsiflexion resistance of an ankle-foot orthosis. Therefore, the aim of this study was to investigate the effects of incremental changes in dorsiflexion and plantarflexion resistance of an articulated ankle-foot orthosis with the Triple Action joints on lower limb joint kinematics and kinetics in individuals post-stroke during gait. Methods: Gait analysis was performed on 10 individuals who were post-stroke under eight resistance settings (four plantarflexion and four dorsiflexion resistances) using the articulated ankle-foot orthosis. Kinematic and kinetic data of the lower limb joints were recorded while walking using a three-dimensional Vicon motion capture system and a Bertec split-belt instrumented treadmill. Findings: Repeated measures analysis of variance revealed that adjustment of plantarflexion resistance had significant main effects on the ankle ( P < 0.001) and knee ( P < 0.05) angles at initial contact, while dorsiflexion resistance had significant ( P < 0.01) main effects on the peak dorsiflexion angle in stance. Plantarflexion and dorsiflexion resistance adjustments appeared to affect the peak knee flexor moment in stance, but no significant main effects were revealed ( P = 0.10). Adjustment of plantarflexion resistance also demonstrated significant ( P < 0.05) main effects in the peak ankle positive power in stance. Interpretation: This study demonstrated that the adjustments of resistance in the ankle-foot orthosis with the Triple Action joints influenced ankle and knee kinematics in individuals post-stroke. Further work is necessary to investigate the long-term effects of the articulated ankle-foot orthoses on their gait. Highlights: An ankle-foot orthosis with Triple Action joints allow adjustment of resistance. The effect of adjustment of its resistance on gait was investigated in individuals post-stroke. Change in plantarflexion resistance significantly affected ankle and knee kinematics. Change in dorsiflexion resistance significantly affected ankle kinematics.